Ultra-flexible semitransparent organic photovoltaics - Lee, Hanbee; Jeong, Soyeong; Kim, Jae Hyun; Jo, Yong Ryun; Eun, Hyeong Ju; Park, Byoungwook; Yoon, Sung Cheol; Kim, Jong H.; Lee, Seung Hoon; Park, Sungjun (npj Flexible Electronics, 2023)
Ultra-flexible organic photovoltaics (OPVs) are promising candidates for next-generation power sources owing to their low weight, transparency, and flexibility. However, obtaining ultra-flexibility under extreme repetitive mechanical stress while maintaining optical transparency remains challenging because of the intrinsic brittleness of transparent electrodes. Here, we introduce strain-durable ultra-flexible semitransparent OPVs with a thickness below 2 μm. The conformal surface coverage of nanoscale thin metal electrodes (< 10 nm) is achieved, resulting in extremely low flexural rigidity and high strain durability. In-depth optical and electrical analyses on ultrathin metal electrodes showed that the devices maintain over 73% of their initial efficiency after 1000 cycles of repetitive compression and release at 66% compressive strain, and the average visible light transmittances remain higher than 30%. To our knowledge, this is the first systematical study on mechanical behaviors of strain-durable ultra-flexible ST-OPVs through precise adjustment of each ultrathin electrode thickness toward the emergence of next-generation flexible power sources.